STAGES OF GREEN HYDROGEN ENERGY DEVELOPMENT OF UKRAINE - Kudria, S.; Riepkin, О.; Rubanenkо, О.; Yatsenko, L.; Shynkarenko, L. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2022)
The paper presents the results of theoretical and applied research and practical achievements of domestic scientists in the field of green hydrogen energy. Due to the ecological advantages of hydrogen technologies, their wide application is one of the promising modern directions of decarbonization of world energy. As a part of the creation of integrated energy systems based on renewable energy sources, since 1980 in Ukraine conducted research on the use of hydrogen as an energy source and storage medium. Various forms of storage and transportation of hydrogen were studied, and the most acceptable methods of accumulation were determined, considering its further use in renewable energy systems: combustion to obtain thermal energy, conversion into electricity in motor generators and fuel cells, use of fuel mixtures with gasoline in motor transport. Based on the analysis of scientific and technical information and practical developments in the field of hydrogen energy, several models of environmentally friendly systems of production, storage, and use of hydrogen of different energy capacity depending on the capacity of RES based on RES were created, their energy parameters, economic indicators, technical and technological support were determined. As a result of joint work of creative teams of Danish and Ukrainian scientists under the agreement between the Folkecenter (Denmark) and the Institute of Electrodynamics of the NAS of Ukraine from 1990 on the basis of scientific and technical solutions for hydrogen production, storage and further conversion into electricity and quality of fuel in vehicles, created the first wind farm in Europe. The results of its further tests became a real basis for the development of a modern environmentally friendly hydrogen energy industry. The results of modern research in the field of green hydrogen energy, energy potential of green hydrogen in Ukraine and prospects for its production and application are presented. The main directions of hydrogen energy development for building a new economic model of Ukraine are aimed at creating a consistent national policy that will ensure the use of green hydrogen as an energy and environmentally efficient energy source as an important component of a carbon-free energy complex. Ref. 20. Fig. 3.